A Review on the Assessment of Radiation Induced Salivary Gland Damage After Radiotherapy - Wu, Vincent W. C.; Leung, Kit Yee (Frontiers in Oncology, 2019)
Head and neck cancers are common in Southern China including Hong Kong. Intensity modulated radiotherapy has been the treatment of choice for these patients. Although radiotherapy provides good local control, radiotherapy treatment side-effects are still inevitable due to close proximity of the organs at risk from the target volume. Xerostomia, which is caused due to the damage of salivary glands, is one of the main radiation induced toxicities in post-radiotherapy head and neck patients. This review article discusses the methods for the assessing of radiation induced salivary gland changes including the gland morphology and saliva flow rate. The discussion also includes the recovery of the salivary gland after radiotherapy and how it is affected by the dose. It is expected that the future direction in monitoring the recovery of salivary glands will focus in cellular or molecular levels, and the development of imaging biomarker